Trypanocidal Activity of Some Medicinal Plants Against the Epimastigotes of Trypanosoma cruzi - AR Gohari; S Saeidnia; A Hadjiakhoondi; A Naghinejad; T Yagura (Institue of Medicinal Plants, ACECR, 2008)
Background: Some of medicinal plants are a potential source of new drugs to improve the treatment of Chagase disease whose treatment is still a challenge. Here in this screening, the in vitro trypanocidal activity of some fractions for 16 medicinal plants, collected from the northern part of Iran, has been reported.   Methods: Aerial parts of the plants were dried carefully and followed by extraction with hexane and methanol, successively, by maceration at room temperature. Different concentrations of the plant extracts in ethanol were investigated against the epimastigotes of T. cruzi. The movement of epimastigotes was observed under a microscope. We assumed that immobilized organisms were died. The negative control contained ethanol in the same proportion utilized to dissolve the drugs. Each assay was performed in duplicate together with gentian violet as a positive control.   Results: Results show that hexane extracts of Rubus hyrcanus and Salvia sclerae have been observed the most activity against the epimastigotes of T. cruzi (MLC = 12.5 m g/ml). None of methanol fractions shows trypanocidal activity except Salvia sclerae (MLC = 50 m g/ml). Echium amoenum, Satureja macrantha, S. atropatana and Stachys laxa did not display activity lower than 100 m g/ml in both hexane and methanol extracts. Conclusions: Some of Iranian medicinal plants (Salvia sclerae, Marrubium vulgare and Rubus hyrcanus) could be the promising source of active components against the epimastigotes of T. cruzi and need to further phytochemical and pharmacological studies.